2020
DOI: 10.1042/cs20200153
|View full text |Cite
|
Sign up to set email alerts
|

Renal functional effects of the highly selective AT2R agonist, β-Pro7 Ang III, in normotensive rats

Abstract: Recently, we designed a group of peptides by sequential substitution of the naturally occurring α-amino acid throughout the Ang III peptide sequence with the corresponding β-amino acid. β-Amino acid substitution at the proline residue of Ang III (β-Pro7-Ang III) resulted in a highly selective AT2R ligand, demonstrating remarkable selectivity for the AT2R in both binding and functional studies. To provide additional functional evidence for the suitability of β-Pro7 Ang III as a novel AT2R agonist, we tested eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Studies in normotensive rat kidneys have demonstrated that Ang III, but not Ang II, induced AT 2 receptor–mediated natriuresis ( Padia et al, 2007 ) and that this effect was mediated via activation of proximal tubule AT 2 receptors via a cGMP-dependent pathway ( Kemp et al, 2012 ). Similar findings have been reported recently in response to a novel β -amino acid substituted Ang III, β -Pro 7 -Ang III, which has high specificity for the AT 2 receptor ( Krause et al, 2020 ). Further, the Ang III–induced AT 2 receptor–mediated natriuretic effect was augmented by the blockade of aminopeptidase N, an enzyme metabolizing Ang III to Ang IV, thereby increasing Ang III levels ( Padia et al, 2007 ; Kemp et al, 2012 ).…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinssupporting
confidence: 89%
See 2 more Smart Citations
“…Studies in normotensive rat kidneys have demonstrated that Ang III, but not Ang II, induced AT 2 receptor–mediated natriuresis ( Padia et al, 2007 ) and that this effect was mediated via activation of proximal tubule AT 2 receptors via a cGMP-dependent pathway ( Kemp et al, 2012 ). Similar findings have been reported recently in response to a novel β -amino acid substituted Ang III, β -Pro 7 -Ang III, which has high specificity for the AT 2 receptor ( Krause et al, 2020 ). Further, the Ang III–induced AT 2 receptor–mediated natriuretic effect was augmented by the blockade of aminopeptidase N, an enzyme metabolizing Ang III to Ang IV, thereby increasing Ang III levels ( Padia et al, 2007 ; Kemp et al, 2012 ).…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinssupporting
confidence: 89%
“…Since AT 2 receptor activation increases renal blood flow but not GFR (Hilliard et al, 2012(Hilliard et al, , 2014Kemp et al, 2014Kemp et al, , 2016, AT 2 receptormediated natriuresis must be due to changes in tubular function rather than renal hemodynamics. Within the proximal tubule, AT 2 receptor-mediated natriuresis is achieved by translocation of AT 2 receptors to the apical plasma membrane of proximal tubular cells (Kemp et al, 2014(Kemp et al, , 2016Krause et al, 2020), inhibition of HCO 3…”
Section: Receptors Involved In the Effects Of Kidney Angiotensinsmentioning
confidence: 99%
See 1 more Smart Citation
“…β-Pro 7 -Ang III also induced encouraging renal vasodilatory and natriuretic effects, a classic AT2R agonist activity, in both male and female normotensive rats. This study highlighted specific roles for the AT2R in the regulation of renal function according to gender since renal vasodilator response was much greater in female rats than males (Krause et al, 2020).…”
Section: Modified Ang IIImentioning
confidence: 75%
“…Unexpectedly, we found that α-to-β replacement could, in some cases, alter the nature of the message, relative to the original α-peptide. Examples included discovery of partner-selective α/β-peptides derived from a promiscuous α-peptide and pathway-selective analogues of peptide hormones (“biased agonists”). , Studies involving backbone modification via α-to-β replacement in derivatives of neuropeptide Y family members, angiotensins, , and phosphopeptides that bind to 14–3–3 proteins provide further evidence that replacing one or a few α residues in a polypeptide with β homologues can generate novel derivatives with interesting properties. , These precedents led us to wonder whether antigen analogues containing an α-to-β replacement might form MHC I complexes that retain the signaling properties of the native pMHC I, as manifested via engagement of TCRs, or perhaps display altered signaling properties.…”
Section: Introductionmentioning
confidence: 99%